Rural Women and Agricultural Extension in the Sahel - Spurling, Daphne (World Bank, Washington, DC, 2012)
Women play a pivotal role in agriculture in the Sahel. In Burkina Faso and Mali, for example, an estimated 93 percent and 78 percent respectively of active women work in agriculture. High levels of rural poverty coupled with a fragile agro-ecological environment make the contribution of women's productive activities to the household and community a crucial element in the survival of the rural population. As patterns of production change and men migrate in search of work, the labor input of women is increasing. Yet only about one participant in five in extension activities in the region is a woman. In all the Sahelian countries, the agricultural service projects funded by the International Development Association (IDA) focused initially on establishing national programs based on Training and Visit (T&V) management principles. With the second generation of these projects coming on line, increased knowledge and systematic documentation of the current and changing roles of women in agricultural production were necessary to improve the targeting of project activities.